Travel behavior before and after COVID-19. A hybrid choice model applied to a panel dataset - Eleonora Sottile; Giovanni Tuveri; Francesco Piras; Italo Meloni (Transportation Research Interdisciplinary Perspectives)
After two decades of psychological research into travel behavior, one would anticipate a thorough understanding of the cognitive processes guiding travel choices. However, the intricate and unpredictable nature of mobility dynamics often obstructs efforts to promote sustainable travel behaviors. While hybrid choice models (HCMs) incorporating latent variables prove invaluable in analyzing travel behavior, there remains a critical need for further exploration into effectively managing these variables. Typically assessed at singular time points, these variables pose challenges in analyzing individual characteristics based on their fluctuations. Moreover, deriving actionable policy implications from HCMs is challenging due to the inherent nature of psycho-attitudinal variables, which exhibit limited responsiveness to alterations in alternatives. Only a significant disruptive event could induce notable shifts in individuals’ psycho-attitudinal characteristics. The objective of this paper is to investigate two aspects: i) to study if and how norms, intentions and perceived behavioral control change after a strong shock such as the pandemic, and ii) to analyze the differences in the HCMs results estimated by using data collected before and after the shock. The study involves a panel dataset gathered during a VTBC Program which involved three phases, two of which before and straight after the first lockdown. Our results show that norms were less impacted by COVID-19 and lost importance post-lockdown. There was a notable decline in the intention to use sustainable modes and an increase in car usage, with significant differences in perceived behavioral control between those who maintain and those who change their transport modes.